2011
DOI: 10.1645/ge-2850.1
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy and Molecular Characterization of A New Haplosporidium Species (Haplosporidia), A Parasite of the Marine Gastropod Siphonaria pectinata (Mollusca: Gastropoda: Siphonariidae) In the Gulf of Mexico

Abstract: Based on scanning electron microscopy and the small subunit ribosomal RNA (SSU rRNA), Haplosporidium tuxtlensis n. sp. (Haplosporidia), a parasite found in the visceral tissues of the false limpet Siphonaria pectinata (Linnaeus, 1758), is described. The spores are ellipsoidal (3.61 ± 0.15 µm × 2.69 ± 0.19 µm), with a circular lid (2.94 ± 0.5 µm) representing the operculum. The spore wall bears filaments occurring singly, or in clusters, of 2 to 8, fusing distally. Phylogenetic relationships of H. tuxtlensis n.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…as the agent of the lesions in the examined specimens of P. nobilis (Catanese et al, 2018). Similar pathological conditions of the digestive gland have also been associated with the sporulation of H. nelsoni and Haplosporidium tuxtlensis in eastern oyster Crassostrea virginica (Gmelin, 1791) and the striped false limpet Siphonaria pectinata (Linnaeus, 1758) (Couch et al, 1966, Vea andSiddall, 2011). Before the MME in Spain, haplosporidan parasites were detected infecting species of bivalves, gastropods, crustacean, worms, ascidians and even hyperparasite trematode larvae (Burreson andFord, 2004, Arzul andCarnegie, 2015), but never in a member of the Pinnoidea Superfamily.…”
Section: Discussionmentioning
confidence: 75%
“…as the agent of the lesions in the examined specimens of P. nobilis (Catanese et al, 2018). Similar pathological conditions of the digestive gland have also been associated with the sporulation of H. nelsoni and Haplosporidium tuxtlensis in eastern oyster Crassostrea virginica (Gmelin, 1791) and the striped false limpet Siphonaria pectinata (Linnaeus, 1758) (Couch et al, 1966, Vea andSiddall, 2011). Before the MME in Spain, haplosporidan parasites were detected infecting species of bivalves, gastropods, crustacean, worms, ascidians and even hyperparasite trematode larvae (Burreson andFord, 2004, Arzul andCarnegie, 2015), but never in a member of the Pinnoidea Superfamily.…”
Section: Discussionmentioning
confidence: 75%
“…They were one of the first groups to be recognized as significant pathogens of bivalve molluscs, with only nelsoni and all the other Haplosporidium, Bonamia, and Minchinia spp. (Reece et al 2004;Azevedo et al 2006;Siddall and Aguado 2006;Bearham et al 2007;Nunan et al 2007;Vea and Siddall 2011;Molloy et al 2012;Stentiford et al 2013;Engelsma et al 2014). While the maximum likelihood analysis of Ituarte et al (2014) found H. louisiana to reside in this position, both that study's parsimony analysis as well as our updated analysis with all the currently characterized haplosporidian species (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Haplosporidians infecting marine molluscs have been widely reported around the world (Burreson & Ford, 2004). Most species parasitising molluscs have been described from bivalves and only four species are known from gastropods: Haplosporidium pickfordi Barrow, 1961 from the freshwater physid snail Physella parkeri (Currier), Haplosporidium lusitanicum Azevedo, 1984 from the limpet Helcion pellucidus Linnaeus, Haplosporidium montforti Azevedo et al, 2006 from the abalone Haliotis tuberculata Linnaeus, and Haplosporidium tuxtlensis Vea & Siddall, 2011, recently described from the striped false limpet Siphonaria pectinata (Linnaeus) in the Gulf of Mexico (Vea & Siddall, 2011).…”
Section: Introductionmentioning
confidence: 99%